1995
DOI: 10.1093/bja/75.6.724
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine balance and immunosuppressive changes at cardiac surgery: contrasting response between patients and isolated CPB circuits

Abstract: In vitro work suggests that IL-10 plays a pivotal role in controlling the balance of pro- and anti-inflammatory cytokines and monocyte HLA-DR expression. In 20 patients undergoing cardiac surgery, we investigated elaboration of interleukin 10 (IL-10) and its relationship to pro- and anti-inflammatory cytokines and leucocyte expression of HLA-DR and adhesion molecules. There were small increases in pro-inflammatory cytokines (IL-1, IL-8 and tumour necrosis factor (TNF) after induction, returning to baseline on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
108
2
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 27 publications
6
108
2
6
Order By: Relevance
“…The current study showed that the cytokine response to open cholecystectomy stimulated both the pro-inflammatory (IL-1, IL-6 and TNF-a) and anti-inflammatory (IL-4) components, while this response was absent in laparoscopic cholecystectomy. This pro-and anti-inflammatory cytokine response has been reported by Gilliland et al during abdominal surgery [15] and by McBride et al during cardiac surgery [16].…”
Section: Discussionsupporting
confidence: 70%
“…The current study showed that the cytokine response to open cholecystectomy stimulated both the pro-inflammatory (IL-1, IL-6 and TNF-a) and anti-inflammatory (IL-4) components, while this response was absent in laparoscopic cholecystectomy. This pro-and anti-inflammatory cytokine response has been reported by Gilliland et al during abdominal surgery [15] and by McBride et al during cardiac surgery [16].…”
Section: Discussionsupporting
confidence: 70%
“…Following administration of fentanyl and heparin during cardiac surgery, no immediate increases were observed in plasma levels of the anti-inflammatory cytokines suggesting perhaps that the drugs did not directly induce an anti-inflammatory response [6]. This present study also looked at the effect of these drugs on the IL-Ira and TNFsr response.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, there is in uitro evidence that administration of TNFcl may induce a later anti-inflammatory IL-I0 response [20]. In this context, it may be significant that the pro-inflammatory response prior to cardiopulmonary bypass is followed by a phased plasma anti-inflammatory response which commences before the termination of bypass [6]. Such a concept of pro-inflammatory cytokine priming is consistent with the present report of fentanyl administration to the monocyte cultures not only leading to a n increase in pro-inflammatory cytokines, but also a significant increase in IL-I ra production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils play a key effector role in systemic inflammation because their activation leads to the production of cytotoxic hydroxyl radicals and proteolytic enzymes 17 . The level of cytokines produced by monocytes increases during and after extracorporeal circulation and orchestrated pro-anti-inflammatory responses 18 . endothelial cells, with their surface of 100 square metres, are effective excretion organs that are closely involved in inflammatory processes 19 .…”
Section: Discussionmentioning
confidence: 99%